A new species of the family Leucothoidae (Crustacea, Amphipoda) from the Mediterranean Sea, Paranamixis fishelsoni sp. nov. - Kaim-Malka, R.a. (Zootaxa, 2024)
A new Paranamixis species, is described based on an anamorph male (adult male on terminal stage), and on a leucomorph specimen which is the shape, in this genus, of the females and also of the males which have not reached the terminal stage. The presence of a Paranamixis species is recorded for the first time in the Mediterranean Sea. A key of the species known is given.